The Role of Knowledge-Oriented Leadership in Fostering Innovation Capabilities: The Mediating Role of Data Analytics Maturity - Destina Ratna Asih Khodijah Kadarsah; Rajesri Govindaraju; Budhi Prihartono (IEEE Access, 2023)
The ability to continuously innovate has been widely realized as crucial for organizations to survive and be sustainable. One of the keys to successful innovation in a turbulent environment is leadership from top management and executives in organizations. Moreover, the role of knowledge-oriented leadership in promoting innovation within organizations has received considerable attention in recent studies. However, past studies have been more focused on the indirect impact of knowledge-oriented leadership instead of the direct impact of innovation capability. Therefore, this study examined both the indirect and direct impacts of knowledge-oriented leadership on fostering innovation capabilities through data analytics maturity. Data were collected from 114 participants working in medium and large organizations across different industries in Indonesia using a web-based questionnaire. Data were analyzed using partial least squares-structural equation modeling (PLS-SEM). Results show that knowledge-oriented leadership has a significant direct impact on innovation capabilities, especially on explorative innovation. The results also show that knowledge-oriented leadership has a strong indirect impact on both explorative and exploitative innovation through data analytics maturity. Hence, this study confirms that as a third-order construct comprising five dimensions (organizational culture, data governance, strategy management, skills and technology), data analytics maturity plays an important role in fostering explorative and exploitative innovation in companies.